ANALISIS SISTEM AKUNTANSI PENCATATAN KAS PADA PT. EXPEDISI BAKUNG PEKANBARU - Hadion Wijoyo (Jurnal AkunStie (JAS), 2020)
In the Accounting System, Cash Receipts will be closely related to the sale of services, if the system is not structured properly it will have a major effect on the amount of cash that will be received by the company. For this reason, the company needs a Cash Receipts Accounting System, because with this system, it can produce good, accurate, and relevant information about the amount of cash receipts received this year or in the future. To create an accurate and good cash register is one way to achieve company goals. The main key of an accounting in achieving its targets is to provide more value, in a good report to the company and give an overview of the company's condition so that the report is more qualified. Petty cash fund is a fund provided by the company's organizational units. This petty cash fund is relatively small and ordinary used for expenses that are not meaningful for example the purchase of office equipment, transportation and others.